High strain rate tensile and compressive effects in glassy polymers - Woodworth B.T.; Siviour C.R.; Jordan J.L. (EPJ Web of Conferences, 2012)
Polymers are increasingly used in impact and complex high rate loading applications. Generally, the mechanical response of glassy polymers under high strain rates has been determined in compression. Some research programs have studied the combined effects of temperature and strain rate, still primarily in compression, providing better understanding of the physics behind the observed response and enhancing the models for these materials. However, limited data are available in tension, and even more limited are data describing both the compressive and tensile response of the same glassy polymer. This paper investigates the compressive and tensile response of glassy polymers across a range of stain rates from quasi-static to dynamic. Experimental results from dynamic mechanical analysis, quasi-static compression and tension, and split Hopkinson tension/pressure bars on several representative glassy polymers will be presented. The pressure dependant yield in these materials will be discussed through comparison of the tensile and compressive yield stresses.